Elements of Probability Theory - Adedokun, Moradeyo (Ile-Ife, Osun, Nigeria: University of Ife press, 1984)
Modern techniques of Probability Theory have been applied to a wide variety of fields in recent years, especially the fields of engineering, science and technology. The main purpose of this book is to provide a brief but detailed exposition of Probability Theory suited to self-study and requiring only an elementary knowledge of Integral and differential Calculus.
ne 14/03/2018
Loan
Keywords: Probabilities